CITATION AND TENSE FOR REVIEWING PREVIOUS RESEARCH IN THE INRODUCTION SECTION OF ENGLISH 1SCIENCE JOURNALS BY NON-NATIVE SPEAKERS (Journal of Research and Educational Research Evaluation, 2012)
AbstractTujuan penelitian ini adalah untuk mengkaji pola sitasi dalam hubungannya dengan pemilihan kala di bagian tinjauan pustaka, khususnya di bagian Pendahuluan untuk artikel jurnal berbahasa Inggris oleh non-penutur asli. Karena penelitian ini hanya membahas satu jenis artikel, yaitu artikel penelitian, Analisis Genre diadopsi. Hasil penelitian menunjukkan bahwa dalam hal jenis sitasi, jumlah IPC (sitasi yang mengacu ke informasi) dalam data jauh lebih dominan daripada APC (sitasi yang mengacu ke penulis) sementara dalam pola yang standar jumlah APC harus lebih banyak daripada IPC karena IPC hanya berfungsi sebagai langkah (move) pembuka untuk tinjauan pustaka. Karena jumlah IPC lebih banyak daripada APC, jumlah kala kini (present tense) juga lebih besar daripada kala lampau (past tense).The aim of this study is to explore the citation pattern in relation to tense choice for reporting past literature in the Introduction section of English research articles by non-native speakers. Since the research dealt with one type of papers, i.e. research articles, Genre Analysis was adopted. The results indicate that in terms of types, IPC (Information Prominent Citation) referring to general areas of research is much more dominant than APC (Author Prominent Citation) referring to specific areas whereas in the standard pattern the number of APC should be more dominant than IPC since IPC only functions as an “opening move” for reporting past literature. As IPC is more dominant than APC, the present tense also outnumbers the past tense.